Simple Technical Trading Rules and the Stochastic Properties of Stock Returns - Brock, William; Lakonishok, Josef; LeBaron, Blake (Journal of Finance, 1992)
This paper tests two of the simplest and most popular trading rules–moving average and trading range break–by utilizing the Dow Jones Index from 1897 to 1986. Standard statistical analysis is extended through the use of bootstrap techniques. Overall, their results provide strong support for the technical strategies. The returns obtained from these strategies are not consistent with four popular null models: the random walk, the AR(1), the GARCH-M, and the Exponential GARCH. Buy signals consistently generate higher returns than sell signals, and further, the returns following buy signals are less volatile than returns following sell signals. Moreover, returns following sell signals are negative, which is not easily explained by any of the currently existing equilibrium models. Copyright 1992 by American Finance Association.(This abstract was borrowed from another version of this item.)